Macropinocytosis: mechanisms and regulation. Issue 5 (15th March 2023) - Salloum, Gilbert; Bresnick, Anne R.; Backer, Jonathan M.
Abstract : Macropinocytosis is defined as an actin-dependent but coat- and dynamin-independent endocytic uptake process, which generates large intracellular vesicles (macropinosomes) containing a non-selective sampling of extracellular fluid. Macropinocytosis provides an important mechanism of immune surveillance by dendritic cells and macrophages, but also serves as an essential nutrient uptake pathway for unicellular organisms and tumor cells. This review examines the cell biological mechanisms that drive macropinocytosis, as well as the complex signaling pathways — GTPases, lipid and protein kinases and phosphatases, and actin regulatory proteins — that regulate macropinosome formation, internalization, and disposition.